A Boron Nitride Nanosheets Composite Membrane for a Long‐Life Zinc‐Based Flow Battery. Issue 17 (5th March 2020) - Hu, Jing; Yue, Meng; Zhang, Huamin; Yuan, Zhizhang; Li, Xianfeng
Abstract: The capability to maintain a constant system temperature is vital in nature, since it endows the system with enhanced lifetime. This trait also works for zinc‐based batteries, because their cycle‐life is limited by notorious zinc dendrite/accumulation, which are highly affected by the inhomogeneous distribution of temperature on electrode and relatively low mechanical strength of membrane. Herein, boron nitride nanosheets (BNNSs) with high mechanical strength serving as heat‐porter are introduced onto a porous substrate to enable uniform deposition of zinc and further a zinc‐based flow battery with long‐cycle life. The results indicate that BNNSs can effectively adjust the deposited zinc from needle‐like to French fries‐like morphology, thus affording the battery with a stable performance for nearly 500 cycles at 80 mA cm −2 . Most importantly, an energy efficiency of above 80 % can be obtained even at 200 mA cm −2, which is by far the highest value ever reported among zinc‐based flow batteries. Abstract : Boron nitride nanosheets (BNNSs) with high thermal conductivity and mechanical strength are introduced onto a porous membrane substrate to induce dendrite‐free zinc deposition and further enable a long‐life zinc‐based flow battery.